Students' Perceptions of a Special Program for Developing Exceptional Talent in STEM. Issue 4 (November 2019) - Wu, I-Chen; Pease, Randal; Maker, C. June
This investigation was to explore perceptions of students who participated in the Cultivating Diverse Talents in STEM project in an R1 university through (a) university-based summer internship program, (b) subsequent school-year research internships, and (c) successive summer workshops or internships. Thirteen high school juniors from diverse backgrounds and low-income families were selected using a series of identification and assessment methods. Both the performance-based and paper-and-pencil assessments were measures of creative problem solving and application of conceptual understandings. A questionnaire was administered after students' participation in the summer internship. The core theme, active involvement in problem solving inspired and motivated students with exceptional talent, was identified, including three categories: (a) academic initiative and engagement, (b) transition preparation, and (c) practical skill development . Strengths of diverse, underrepresented students with exceptional talent in STEM (spatial analytical skills, high academic resilience, and persistence) and critical elements of a quality STEM program (focusing on individual research interests and real-world problems, providing enriched and varied experiences, and creating supportive mentoring relationships) are included in the research implications.